Drama dan Teater: Dua Wajah Dari Saru Karya dalam Sastra Indonesia - Firda Mardatillah; Anisa Amanah; Baiq Nia Septiani (Lembaga Einstein College (LEC), 2026)
This study aims to clarify the conceptual differences between drama and theater, which are often misunderstood by the public, and to provide practical guidance in reading drama scripts as the basis for performances. The study uses a descriptive qualitative method with a literature study approach, through the collection and analysis of data from various relevant books and scientific journals. The results of the study indicate that drama is a literary work in the form of a written script containing dialogue, plot, characters, and conflict as a reflection of human life, while theater is a form of realization or performance of the script on stage that involves elements of movement, sound, expression, and collaboration of various arts. The differences between the two lie in the aspects of media, interaction, and their constituent elements, where drama focuses on the text, while theater focuses on the performance. In addition, this study emphasizes the importance of drama script reading techniques that include clarity of articulation, accuracy of intonation, volume control, and the use of appropriate expressions and gestures to support the delivery of meaning. These findings are expected to serve as a reference for actors, directors, and educators in understanding the relationship between drama and theater and improving the quality of performances and literary learning